2015
DOI: 10.1118/1.4928600
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: A Monte Carlo study of magnetic‐field‐induced radiation dose effects in mice

Abstract: Purpose: Magnetic fields are known to alter radiation dose deposition. Before patients receive treatment using an MRI-linear accelerator (MRI-Linac), preclinical studies are needed to understand the biological consequences of magnetic-field-induced dose effects. In the present study, the authors sought to identify a beam energy and magnetic field strength combination suitable for preclinical murine experiments. Methods: Magnetic field dose effects were simulated in a mouse lung phantom using various beam energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…On the other hand, the increase of D max in the HN case is only 1.6% (1.24 Gy). In a recent paper that used a Monte-Carlo analysis of the dose effect of magnetic field on human lung and mouse lung phantoms, Ashley et al 16 observed a dose increase of 45% at the tissue-to-lung interface and a dose decrease of 41% at the lung-to-tissue for a single beam orientation. However, these large dose changes are not observed in the cases we studied where multiple beam orientations are used.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increase of D max in the HN case is only 1.6% (1.24 Gy). In a recent paper that used a Monte-Carlo analysis of the dose effect of magnetic field on human lung and mouse lung phantoms, Ashley et al 16 observed a dose increase of 45% at the tissue-to-lung interface and a dose decrease of 41% at the lung-to-tissue for a single beam orientation. However, these large dose changes are not observed in the cases we studied where multiple beam orientations are used.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetric effect of a transverse magnetic field (TMF) in phantom and patients has been studied extensively . Compared to conventional external beam RT without magnetic field, the magnetic field can generally lead to an altered buildup depth, and a larger, slightly shifted (asymmetric) penumbra arising from tilting of the dose kernel .…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of these changes on dose distribution for radiotherapy treatment with a magnetic field have been studied by many groups using analytical, simulation and/or experimental techniques. [13][14][15] Largely, the focus has been on changes to the spatial distribution of dose resulting from the magnetic field influence on charged particle transport. The high magnetic field strength can have significant perturbations on dose distributions, such as changes to the percentage depth dose, tissue interface effects and lateral shifts in dose distributions in the photon beam radiotherapy.…”
Section: Introductionmentioning
confidence: 99%